Author Correction: Limitation of Fermi level shifts by polaron defect states in hematite photoelectrodes - Christian Lohaus (Nature Portfolio, 2018)
The original version of this Article contained an error in Fig. 2b in which the bottom of the pink-shaded conduction band region was incorrectly positioned at a value of 1.75 eV. The correct conduction band minimum has a value of 2.2 eV. This has now been corrected in both the PDF and HTML versions of the Article.